Pogledi na sjever: hrvatski putopisci u Skandinaviji 1930ih - Tomić, Janica (Array, 2013)
The paper compares two Croatian travelogues, Through Scandinavia (1939) by A. Messner-Sporšić and Through Northern Countries and Cities (1937) by S. Batušić, using narrative categories developed by Dean Duda in his analyses of travel writing. The differences so traced place Messner-Sporšić's text closer to the documentary pole of travelogues, while analysis of Batušić's higly subjective view of the space confirm previous characterizations of his travel writing as distinctly modernist. Rare instances of sublime imagery of natural sights (e.g. Lofoten) in Batušić's text are interpreted in the light of influence of K. Hamsun's writing on the Croatian author. The last segment of the paper shows a similar (and possibly long-lasting) pattern in these otherwise very different projections of Scandinavia: the journey home represented as a return from 'the lightness' to 'the dark'.